2020
DOI: 10.1101/2020.06.30.180042
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hidden introductions of freshwater red algae via the aquarium trade exposed by DNA barcodes

Abstract: ABSTRACTThe global aquarium trade can introduce alien freshwater invaders, potentially impacting local aquatic ecosystems and their biodiversity. The role of the aquarium trade in spreading freshwater red macroalgae that hitchhike on ornamental aquatic plants and animals is unassessed. We investigated this human-mediated phenomenon via a broad biodiversity survey and genetic analysis of freshwater red algae in the field and aquarium shops in East Asia. Using rbc Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(26 citation statements)
references
References 61 publications
5
21
0
Order By: Relevance
“…As a turf-like diploid sporophyte (also known as chantransia; Figure 1B), the alga produces mostly asexual monospores and vegetative fragments (which can attach to other aquatic organisms and surfaces) and rarely sexual meiospores (Kato et al, 2009). In fact, the specimens of M. macrospora previously observed in a survey of Taiwan aquaria and streams were mostly spore-producing chantransia (Zhan et al, 2021).…”
mentioning
confidence: 96%
See 4 more Smart Citations
“…As a turf-like diploid sporophyte (also known as chantransia; Figure 1B), the alga produces mostly asexual monospores and vegetative fragments (which can attach to other aquatic organisms and surfaces) and rarely sexual meiospores (Kato et al, 2009). In fact, the specimens of M. macrospora previously observed in a survey of Taiwan aquaria and streams were mostly spore-producing chantransia (Zhan et al, 2021).…”
mentioning
confidence: 96%
“…including Hat Ya (southern Thailand, Mayla Peninsula), Hong Kong, Taiwan, and Okinawa (Japan). A genetic analysis based on the plastid marker rbcL suggested that there were at least two independent introductions of M. macrospora into East Asia (Zhan et al, 2021). One of the introductions was revealed by a haplotype in aquarium shops in Taiwan and Japan, and the other introduction by a different haplotype in aquarium shops in Hong Kong and Thailand (Zhan et al, 2021).…”
mentioning
confidence: 99%
See 3 more Smart Citations